Pekerja Perempuan di Sektor Informal: Kajian Etnografis Pedagang Asongan di Pasar Tanah Abang Jakarta - Fanisa Pitamouldi; Suyanto Suyanto; Riris Tiani (Prodi Antropologi Fakultas Ilmu Budaya Universitas Diponegoro, 2021)
This study aims to determine ten female workers in fulfilling family needs. In this study, from a gender perspective, feminism is quite well established in coloring the activities of women workers by showing a shift in gender values due to social construction. This type of research is a qualitative descriptive study. Data collection techniques used in-depth interviews, observation, documentation and supporting materials; previous research, and books or other references. The subjects in this study were women workers as informal entrepreneurs in Tanah Abang Market, Jakarta. The selection of subjects was done by using phenomenological qualifier method. The results study show that there are various reasons and motivations for women to work, each of which has an impact as well as knowing the pattern of relationships and describing the decision-making process in the family as an informal business actor. These decisions vary, the majority is to help their husbands to support their daily needs. But it is undeniable that there are other decisions, namely because of an invitation from a relative or to spend spare time to support the family in the village. In accommodating the demands of two roles, women workers also have the burden of dual roles, namely as a mother and wife to their husbands, and women who work in the public sector as breadwinners. The efforts of women workers in overcoming the effects of multiple roles are good time management, using their free time with their families, participating in various social activities in the environment and for resting. Basically they work to help improve their family's economy